2021
DOI: 10.1177/08948453211020124
|View full text |Cite
|
Sign up to set email alerts
|

Am I Gonna Get a Job? Graduating Students’ Psychological Capital, Coping Styles, and Employment Anxiety

Abstract: Thoughts about life after school can be frightening for college students. The uncertainty about employment expectancies can engender crippling anxiety, especially in a time of a major pandemic—COVID-19, and urgent attention is needed. This study, drawing on the self-determination theory, demonstrates preliminary protective effect of positive psychological capital (PsyCap) on employment anxiety among a relatively understudied group—graduating college students (Chinese sample = 546). It further illustrates the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 44 publications
2
67
0
1
Order By: Relevance
“…Previously, researchers have found the association between IU and the development of maladaptive coping strategies [ 57 , 58 ]. Possible explanation to the present finding is that IU is one of the predictors of anxiety symptoms and heightened worry [ 59 ], whereas those who have severe anxiety usually prefer maladaptive coping strategies [ 60 , 61 ]. It is also likely that people who prefer maladaptive coping strategies have an escape coping motive, so they are more easily to rely on the online activities [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, researchers have found the association between IU and the development of maladaptive coping strategies [ 57 , 58 ]. Possible explanation to the present finding is that IU is one of the predictors of anxiety symptoms and heightened worry [ 59 ], whereas those who have severe anxiety usually prefer maladaptive coping strategies [ 60 , 61 ]. It is also likely that people who prefer maladaptive coping strategies have an escape coping motive, so they are more easily to rely on the online activities [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the study's cross-sectional design with self-reported data raises the possibility of biased reports. However, self-report data on university students' mental health has been adjudged an adequate assessment as individuals are in the best position to evaluate their subjective wellbeing [48,64]. Second, given that the design was cross-sectional, a comparative analysis of international students' mental health across different time points during the pandemic is not possible.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Many studies have addressed the stress levels of university students caused by factors such as the pressure to achieve certain qualifications or continuous working pressure [53,54]. In addition, a good adaptation to the university environment is needed, and uncertainty about the future is always present [19,55].…”
Section: The Role Of Mindfulness In Emotions and Concerns In University Fieldmentioning
confidence: 99%